2009
DOI: 10.1029/2009tc002506
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the exhumation history of the Lesser Himalaya, NW India, from a multitechnique provenance study of the foreland basin Siwalik Group

Abstract: This research presents the first multitechnique provenance study of the Siwalik Group in the Himalayan foreland basin in India, using the Jawalamukhi section, magnetostratigraphically dated at 13–5 Ma. Combined with provenance data from a Dharamsala Formation sedimentary section (21–13 Ma) located close by, it forms the longest temporally continuous record of Himalayan erosion in the Indian foreland basin. Sandstone petrography and heavy mineral analysis, conglomerate clast composition, Ar‐Ar dating of detrita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(131 citation statements)
references
References 65 publications
12
116
2
Order By: Relevance
“…Cooling of leucogranite bodies at ∼16 Ma (Horton and Leech, 2013) along the MCT was linked to cessation of movement and southward propagation of the thrust belt (Jessup et al, 2006). Finally, foreland basin deposits show a dramatic decrease in Himalayan exhumation rates at ∼17 Ma, as shown by a shift in lag times between the depositional ages of samples and the ArAr ages of the youngest detrital white micas (White et al, 2002;Najman et al, 2009).…”
Section: Implication For Geochemical Evolution Of Neogene Paleoseawatermentioning
confidence: 93%
See 2 more Smart Citations
“…Cooling of leucogranite bodies at ∼16 Ma (Horton and Leech, 2013) along the MCT was linked to cessation of movement and southward propagation of the thrust belt (Jessup et al, 2006). Finally, foreland basin deposits show a dramatic decrease in Himalayan exhumation rates at ∼17 Ma, as shown by a shift in lag times between the depositional ages of samples and the ArAr ages of the youngest detrital white micas (White et al, 2002;Najman et al, 2009).…”
Section: Implication For Geochemical Evolution Of Neogene Paleoseawatermentioning
confidence: 93%
“…Recent studies in the Himachal Himalaya (White et al, 2002;Najman et al, 2009) also posit unroofing of a younger succession starting around 17 Ma, prior to erosional exposure of the older rocks of the lower Lesser Himalayan succession at 11 Ma. In particular, they demonstrate that a fundamental shift in petrologic and thermochronological character of foreland basin deposits takes place at ∼17 Ma, where strata record a shift from sediment sourced from higher-grade GH rocks to low-grade sedimentary sources (mostly carbonate and shale).…”
Section: Evidence For ∼16 Ma Exhumation Of the Upper Lh Succession Anmentioning
confidence: 94%
See 1 more Smart Citation
“…Along the Nepal Himalaya, geochronological studies have established depositional age from 13.2 Ma spanning a period till 1 Ma (DeCelles et al 1998a, b;Ojha et al 2000;DeCelles et al 2001DeCelles et al , 2004Szulc et al 2006;Chirouze et al 2012), which corresponds to the age ranges yielded by paleomagnetic studies (Appel et al 1991;Harrison et al 1993;Gautam and Rösler 1999;Gautam et al 2012). Similarly, there are number of milestone works in the northwestern Himalaya that interlinked the erosional records of the foreland basin with tectonic history (Burbank et al 1996;Najman et al 2004;Jain et al 2009;Najman et al 2009). These studies revealed that sediments in the foreland basin have been transported from the Lhasa terrane, Gangdese batholiths, Indus-Tsangpo suture zone, ultra-high-pressure gneiss terrane and Tethys Himalaya until Early Miocene time.…”
Section: Introductionmentioning
confidence: 95%
“…However, a similar study in the Nepal Himalaya has shown that Neogene foreland basin sediments were mainly derived from the Lesser Himalaya, Higher Himalaya and Tethys Himalaya (DeCelles et al 1998a). Recently, a number of studies have been carried out in the Nepalese foreland basin to constrain the exhumation history of the source region using zircon and apatite fission track dating ) and Ar-Ar dating Najman et al 2009;Chirouze et al 2012).…”
Section: Introductionmentioning
confidence: 99%